Kinetics for the Amine-Catalyzed Carbamate Reaction of Tolylene-2,4-diisocyanate - Cheng, Jin-Yong; Yang, Peng-Fei; Li, Tian-Duo; Li, Jun-Ying (Asian Journal of Chemistry, 2011)
Tolylene-2,4-diisocyanate (2,4-TDI) 1 reacts with alcohols through two simultaneous paths in the polyurethane reaction, which generate two different intermediates and one final producttolylene- 4-carbamatic-2-isocyanate 2, tolylene-2-carbamatic-4-isocyanate 3 and tolylene-2,4- dicarbamate 4. The -CH3 chemical shifts in benzene ring in compounds 1, 2, 3 and 4 can be easily tested, well distinguished and quantified. Combined with the results of FT-IR in situ, its kinetics is investigated and four rate constants for the tolylene-2,4-diisocyanate carbamate reaction with isopropanol are calculated out.